The Application of the Internet of Things Framework in the Ideological and Political Teaching System - Bei Qiu; Pakiza Ikram (Journal of Mathematics)
This study uses Internet of Things technology to build a smart system for ideological and political education in order to remove several flaws in present ideological and political teaching. Furthermore, to achieve intelligent monitoring of the ideological and political classroom, this research uses a technique based on IGHT edge feature matching and the ideological and political classroom monitoring image monitoring calculation formula to compute the image light reflection angle. In addition, this paper adopts the method of adaptively obtaining segmentation threshold (OTSU algorithm) to binarize the differenced image. After constructing the smart teaching system, this paper conducts a systematic evaluation based on the simulation experiment. The research results show that the ideological and political teaching system based on the Internet of Things technology proposed in this paper has a good simulation teaching effect, and the system can be used in the follow-up ideological and political teaching to improve the teaching effect.